2021
DOI: 10.1055/a-1709-5271
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Neutrophil Extracellular Traps in Coronary Thrombi of Patients with ST-Elevation Myocardial Infarction

Abstract: Aims: The mechanisms of coronary thrombosis can influence prognosis after STEMI and allow for different treatment groups to be identified; an association between neutrophil extracellular traps (NETs) and unfavorable clinical outcomes has been suggested. Our aim was to determine the role played by NETs in coronary thrombosis and their influence on prognosis. The role of other histological features in prognosis and the association between NETs and bacteria in the coronary thrombi were also explored. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In MI, NET structures as well as citrullinated histone H3 (CitH3)‐positive, that is, NETosis‐primed, neutrophils are abundant in intracoronary thrombi and injured myocardium 138,187 . NET content in intracoronary thrombi is associated with adverse cardiac outcome in human patients with MI, 188–190 and levels of circulating dsDNA are associated with microvascular obstruction in MI patients undergoing percutaneous coronary intervention 191 . Blockers of NET formation (peptidyl arginine deiminase (PAD)4 inhibitors) or enzymes (e.g., DNAse) disrupting histones have become available for research purposes 192,193 and reduced infarct size in mice 194 .…”
Section: Neutrophils In Myocardial Infarctionmentioning
confidence: 99%
“…In MI, NET structures as well as citrullinated histone H3 (CitH3)‐positive, that is, NETosis‐primed, neutrophils are abundant in intracoronary thrombi and injured myocardium 138,187 . NET content in intracoronary thrombi is associated with adverse cardiac outcome in human patients with MI, 188–190 and levels of circulating dsDNA are associated with microvascular obstruction in MI patients undergoing percutaneous coronary intervention 191 . Blockers of NET formation (peptidyl arginine deiminase (PAD)4 inhibitors) or enzymes (e.g., DNAse) disrupting histones have become available for research purposes 192,193 and reduced infarct size in mice 194 .…”
Section: Neutrophils In Myocardial Infarctionmentioning
confidence: 99%
“…Since NETs are not only involved beneficially in the antimicrobial defense but also adversely contribute to the pathogenesis of various disorders, in particular cardiovascular diseases (CVDs), they have been investigated in patients and preclinical disease models of CVDs [ 12 , 13 ]. NETs and associated circulating blood components were found to indicate severe coronary atherosclerosis in a prothrombotic state [ 14 ] as well as the extent and prognosis of myocardial infarction [ 15 , 16 ]. Further studies revealed that NETs are also involved in the pathomechanism of abdominal aortic aneurysms; NET inhibition in a murine AAA model suggested an essential role of NETs in the initial disease phase and identified IL-1β as an inducer of NET formation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting NETosis or degrading existing NETs (or associated mechanistic pathways) have been extensively investigated in many disease models associated with NETs and thrombosis (27)(28)(29)(30). NETosis starts from the activation of NADPH oxidase (NOX) complex via protein kinase C (PKC)-Raf/MERK/ERK by external stimuli, followed by activation of MPO, NE and PAD4.…”
Section: Accepted Manuscriptmentioning
confidence: 99%